Adaptation of Islamic Law in the Halal Lifestyle Trend: A Study of Changes in Community Consumption Behavior - Afifuddin Idrus; Nikmaturrohmah Nikmaturrohmah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The advancement of globalization and modernization has driven significant transformations in the consumption patterns of Indonesian society, which is predominantly Muslim, where Islamic law dynamically adapts through ijtihad and contextual approaches to respond to the halal lifestyle trend that has evolved from a mere religious obligation into a comprehensive way of life encompassing various sectors. This study employs a qualitative method with a literature review approach. The dynamic, flexible, and contextual adaptation of Islamic law in responding to the halal lifestyle trend has encouraged a transformation in consumer behavior toward greater awareness of spiritual, ethical, and sustainability values, while also generating broad social and economic implications, including the strengthening of religious identity, the growth of the halal industry, and increased economic competitiveness, despite ongoing challenges such as access inequality, commodification, and the need for standardization that must be addressed collaboratively.